Analisis Tingkat Kematangan Sistem Pemerintahan Berbasis Elektronik (SPBE) pada Pemerintah Provinsi Sulawesi Selatan - Endang Sri Hidayah; Muzzaman Almadani (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2022)
Abstract The application of Information Technology is currently very influential in people's lives with the aim of achieving a world-class bureaucracy where governance is more effective, efficient, transparent, and accountable and the quality of public services is easier, faster, and affordable. One of them is the implementation of the SPBE (Electronic-Based Government System). The South Sulawesi Provincial Government implements the development of E-Government by implementing SPBE in its work process. The implementation of SPBE has had a great impact on the Provincial Government which is the benchmark for Regional Apparatuses, as well as during the COVID-19 Pandemic which required civil servants to work from home (work from home). This research is an observational study that combines field data with library data and is equipped with an interview study to obtain maximum results. In accordance with the research objectives, namely to identify the maturity level of information technology in South Sulawesi Province. The results of the writing show that the SPBE maturity level of the South Sulawesi Provincial Government has an index value of 2.05 with the predicate